Gating of spontaneous somatic sensations by movement. (September 2014) - Beaudoin, Rachel; Michael, George A.
Abstract Movement is known to attenuate the perception of tactile stimuli delivered on the moving part of the body, and this gating diminishes the greater the distance from the moving part. However, does it influence the perception of sensations occurring spontaneously without external triggers? In Experiment 1, participants were asked to focus on one hand while moving or not moving their thumb, and thereafter to map and describe the spatial and qualitative attributes of sensations perceived over the remaining, motionless part of the hand. The results show that movement reduces the frequency, spatial extent, and intensity of sensations, but also participants' confidence about their spatial characteristics. As expected, gating decreased the greater the distance from the moving thumb. Furthermore, gating was greater for distal than proximal segments of the hand, suggesting a hierarchical proximo-distal suppression. Experiment 2 ruled out the possibility that these effects were due to tactile sensations elicited by movement. Possible mechanisms of gating in the case of spontaneous sensations are discussed.